Analysis of the effect of heel effect on radiation dose distribution in breast and thyroid organs in lumbar radiographic examination - Suherman Hadi Saputro; Olivia Ganna (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Lumbar radiography is a common procedure but poses a risk of radiation exposure to sensitive organs such as the breast and thyroid. This study analyzed the effect of the Heel Effect on the distribution of radiation doses in these organs using an experimental method with an acrylic phantom and an ALOKA pen-dosimeter. Measurements were made on anteroposterior (AP) and lateral (LAT) projections with variations in the orientation of the anode-cathode. The results showed that the cathode orientation produced a higher radiation dose than the anode, with the highest dose in the thyroid at the lateral projection of the cathode orientation (18.8 ± 1.30 μSv) and the lowest at the anode orientation AP projection (5.2 ± 0.83 μSv). The study concluded that the understanding of the Heel Effect can be used to optimize dose distribution according to ALARA principles in diagnostic radiology practice.